2021
DOI: 10.1038/s41598-021-83411-w
|View full text |Cite
|
Sign up to set email alerts
|

The pressure-enhanced superconducting phase of Sr$$_x$$–Bi$$_2$$Se$$_3$$ probed by hard point contact spectroscopy

Abstract: The superconducting systems emerging from topological insulators upon metal ion intercalation or application of high pressure are ideal for investigation of possible topological superconductivity. In this context, Sr-intercalated Bi$$_2$$ 2 Se$$_3$$ 3 is specially interesting because it displays pressure induced re-entrant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
(22 reference statements)
1
5
0
Order By: Relevance
“…This absence of superconductivity on the surface has been a problem in many STM experiments performed on doped Bi 2 Se 3 superconductors, but the present study found that during the prolonged scanning of the tip on the Sr x Bi 2 Se 3 surface, the tip will always accumulate micro-flakes of Sr x Bi 2 Se 3 which show superconductivity. This finding helps to clarify some discrepancies in the observed SC gaps in earlier STM studies [13,14,16], which were inconsistent with the bulk T c . Note that our experimental observation is essentially consistent with those on superconducting Tl-doped Bi 2 Te 3 and Nb-doped Bi 2 Se 3 reported by Wilfert et al [17], who concluded that superconductivity does not extend to the surface in these superconductors.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…This absence of superconductivity on the surface has been a problem in many STM experiments performed on doped Bi 2 Se 3 superconductors, but the present study found that during the prolonged scanning of the tip on the Sr x Bi 2 Se 3 surface, the tip will always accumulate micro-flakes of Sr x Bi 2 Se 3 which show superconductivity. This finding helps to clarify some discrepancies in the observed SC gaps in earlier STM studies [13,14,16], which were inconsistent with the bulk T c . Note that our experimental observation is essentially consistent with those on superconducting Tl-doped Bi 2 Te 3 and Nb-doped Bi 2 Se 3 reported by Wilfert et al [17], who concluded that superconductivity does not extend to the surface in these superconductors.…”
Section: Discussionsupporting
confidence: 58%
“…Han et al [13] used ARPES to demonstrate that the TSS of their Sr x Bi 2 Se 3 samples was intact and the STS data showed a superconducting gap, but their data are also fully compatible with a superconducting flake having been transferred to the tip. The superconductivity observed on the surface of Sr x Bi 2 Se 3 by STM in the works by Kumar et al [16] and Du et al [14] showed values of ∆, T c , and µ 0 H c2 that are incompatible with the bulk values; this problem can be straightforwardly reconciled if a superconducting flake was present on the tip. Interestingly, Kumar et al [16] also performed hard pointcontact spectroscopy and found an increase in T c with increasing pressure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This manifests itself by a pair of indirect finite-energy anti-crossings of BdG bands signaling pairing of quasi-particles having high total angular momenta with quasi-holes possessing lower angular momenta. The phenomenon may be experimentally detectable through tunneling spectroscopy [64][65][66][67] and angle-resolved photoemission spectroscopy [68].…”
mentioning
confidence: 99%